Preschoolers' Anticipation of Sadness for Excluded Peers, Sympathy, and Prosocial Behavior. Issue 5 (3rd September 2018) - Sette, Stefania; Colasante, Tyler; Zava, Federica; Baumgartner, Emma; Malti, Tina
Abstract: We investigated the relations between anticipation of sadness for excluded peers, sympathy, and prosocial behavior in a sample of 127 Italian preschoolers ( Mage = 4.84 years, SD = 0.85). Children attributed emotions to hypothetical excluded peers who exhibited withdrawn versus aggressive behavior, and these attributions were coded for the presence and intensity of sadness. Teachers rated children's sympathy and prosocial behavior via questionnaire. In general, children attributed more sadness to the withdrawn excluded peer than the aggressive excluded peer. A path analysis revealed that those who anticipated higher levels of sadness for the withdrawn excluded peer were rated higher in sympathy and, in turn, higher in prosocial behavior. Attributing high levels of sadness to withdrawn excluded peers—who portray relatively heightened need—may be an early social-emotional characteristic of children who are more sympathetic and more likely to channel other-oriented concerns into prosocial actions.